An Electrically Driven and Readable Molecular Monolayer Switch Based on a Solid Electrolyte. (28th October 2015) - Marchante, Elena; Crivillers, Núria; Buhl, Moritz; Veciana, Jaume; Mas‐Torrent, Marta
Abstract: The potential application of molecular switches as active elements in information storage has been demonstrated through numerous works. Importantly, such switching capabilities have also been reported for self‐assembled monolayers (SAMs). SAMs of electroactive molecules have recently been exploited as electrochemical switches. Typically, the state of these switches could be read out through their optical and/or magnetic response. These output reading processes are difficult to integrate into devices, and furthermore, there is a need to use liquid environments for switching the redox‐active molecular systems. In this work, both of these challenges were overcome by using an ionic gel as the electrolyte medium, which led to an unprecedented solid‐state device based on a single molecular layer. Moreover, electrochemical impedance has been successfully exploited as the output of the system.